Factors associated with parental acceptance of influenza vaccination for their children: the evidence from four cities of China - Mingyi Zhao; Haiyan Liu; Shujuan Qu; Li He; Kathryn S. Campy (Taylor & Francis Group, 2021)
Background It is necessary and urgent to vaccinate 245 million Chinese children against influenza pandemics. The main purpose of this study was to evaluate different psychological and demographic factors that influence parental willingness to vaccinate their children against influenza. Methods A hybrid theoretical framework was expanded and verified with 462 sample data collected from four cities in China. Structural equation models were used to test nine theoretical hypotheses, and the non-standardized coefficient method was used to discuss the moderating effects among demographic variables. Results Knowledge is considered to be the significant factor of performance expectancy (β = 0.228), effort expectancy (β = 0.227) and perceived risk (β = −0.138), and social inﬂuence also has the significant impacts on the above three variables, with β values of 0.437, 0.386, and −0.172. Performance expectancy (β = 0.402), effort expectancy (β = 0.343), and perceived risk (β = −0.244) thus significantly affect parental behavioral intention regarding children's influenza vaccination. Gender, education, and kids' gender are demographic variables with significant moderating effects, while age, income, number of kids are not significant. Conclusion To improve the acceptability of influenza vaccination among Chinese children, the promoting policies should emphasize on public knowledge and social inﬂuence, as well as effectiveness, affordability, and safety of vaccination.